OPTIMIZATION OF GROWTH CONDITIONS OF DIFFERENT ALGAL STRAINS AND DETERMINATION OF THEIR LIPID CONTENTS - N. Munir; A. Imtiaz; N. Sharif; S. Naz (Journal of Animal and Plant Sciences, 2015)
Aim of the present study was collection and identification of native algal species, optimization of their growth conditions and comparison of their oil content. From the collected 20 samples 3 different algal species were identified. The effect of growth media, temperature, pH level, light intensity and aeration on growth of Spirogyra sp. and Oedogonium sp. and Chlorella sp. was recorded. It was observed that both Oedogonium sp. and Chlorella sp. grow well in Blue green medium while Spirogyra sp. showed better growth in terms of fresh weight in Bold Basal medium.  Algal growth optimum temperature was between 24-28 oC. It was also observed that neither very low nor very high pH is suitable for algal growth and at pH 7.5 algae were able to grow at maximum with fresh weights of 4.89±0.091 g and 4.79±0.021 g for Spirogyra sp. and Oedogonium sp. respectively. Artificial fluorescent light resulted in an increased growth of algae as compared to sunlight or when algae placed near window and exposed to indirect sunlight. The oil content of the three algal species is in order Chlorella sp > Oedogonium sp. Spirogyra sp. Hence, Chlorella sp. was found to have the highest lipid content with 15.46±0.240% yield for lipid content.
Keywords: Algae; Biofuel; Chlorella.; Oedogonium.; Optimization; Spirogyra